1996
DOI: 10.1111/j.1472-765x.1996.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of different isolates of Vibrio harveyi in tiger prawn, Penaeus monodon

Abstract: P.‐C. LIU, K.‐K. LEE AND S.‐N. CHEN. 1996. The pathogenicity of six Vibrio harveyi strains in tiger prawn, Penaeus monodon, was studied, using both live bacteria and extracellular products (ECP). The organisms originally isolated from diseased penaeids were more virulent using both live bacteria and ECP (LD50, 4.87–8.65 times 104colony‐forming units (cfu) and 1.20–1.51 μg protein g‐1body weight) than the two reference strains originally isolated from either sea water (ATCC 25919; LD50, 3.18 times 106cfu and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
137
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 22 publications
5
137
1
8
Order By: Relevance
“…After incubation at 24 1C for up to 7 days, the presence of zones of clearing around the colonies were recorded as a positive phenotype. Phospholipase activity was examined as previously described (Liu et al, 1996). Overnight cultures were inoculated on tryptone soya agar supplemented with 1% egg yolk emulsion (Oxoid) with incubation at room temperature for up to 7 days.…”
Section: Pathogenicity Testsmentioning
confidence: 99%
“…After incubation at 24 1C for up to 7 days, the presence of zones of clearing around the colonies were recorded as a positive phenotype. Phospholipase activity was examined as previously described (Liu et al, 1996). Overnight cultures were inoculated on tryptone soya agar supplemented with 1% egg yolk emulsion (Oxoid) with incubation at room temperature for up to 7 days.…”
Section: Pathogenicity Testsmentioning
confidence: 99%
“…Accordingly, it can cause the "milky seas" effect, in which a uniform blue glow is emitted from the seawater and which is apparent during the night. Sometimes the glow covers nearly 16,000 km 2 . In marine ecosystems, chitin-containing substances are major sources of carbon and nitrogen for marine vibrios.…”
mentioning
confidence: 99%
“…It is found free-living in tropical marine waters and also commensally as a component of the gut microflora of marine animals. The bacterium is both a primary and an opportunistic pathogen of marine animals, triggering a lethal disease called luminous vibriosis (1), which affects marine fish and prawn-farming operations worldwide (2,3). V. harveyi is a fast growing bacterium under both aerobic and anaerobic conditions.…”
mentioning
confidence: 99%
“…Crop rotation in shrimp aquaculture is worth exploring and may prove feasible in view of the recent findings on the host specificity/preference of certain strains of Vibrio harveyi. Liuxy et al (1996) found differences in the pathogenicity of Vibrio harveyi isolated from penaeid and non-penaeid sources. Keeping this in mind, in the present study finfishes (Mugil cephalus and Chanos chanos) were cultured between crops of Litopenaeus vannamei shrimps for crop rotation and the reduction in the incidence of shrimp diseases was observed.…”
Section: Introductionmentioning
confidence: 98%